TINJAUAN PUSTAKA SISTEMATIS PENERAPAN INTERAKSI MANUSIA DAN KOMPUTER DALAM APLIKASI GAME MOBILE LEGENDS - Romadhona, Wahyu; Sarif Surorejo; Bangkit Indarmawan Nugroho (Lembaga Pengembangan Kinerja Dosen, 2022)
This study uses the idea of ​​human-computer interaction (HCI) to provide options for the Mobile legends game. The results of this study are the concept of Human Computer Interaction (HCI) which is used to describe HCI in the Mobile legends game but has not been implemented due to incomplete sources of previous research, usability implementation, system functions, effectiveness, and efficiency. Designing human and computer interactions in the mobile legends game while still paying attention to the basics of HCI is the author's suggestion for researchers who will develop HCI